2016
DOI: 10.2217/pgs-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic and Personalized Approaches to Tackle Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a raising liver disease with increasing prevalence due to the epidemics of obesity and diabetes, with end points in cirrhosis or hepatocellular carcinoma. A multitude of genetic and metabolic perturbations, together with environmental factors, likely drive the disease. However, to date only a few genes, primarily PNPLA3 and TM6SF2, associate with NAFLD and there is no specific treatment. In this review we focus on the therapeutical aspects of NAFLD, taking into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 151 publications
0
18
0
Order By: Relevance
“…Understanding the host genetic factors that may influence response to a certain therapeutic agent may therefore allow a more effective and personalized delivery of therapy to patients with NASH who have a high chance of response. It may also spare patients with a low chance of response the exposure to a therapeutic agent that they may not respond to and also spare them the side effects of such agent …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the host genetic factors that may influence response to a certain therapeutic agent may therefore allow a more effective and personalized delivery of therapy to patients with NASH who have a high chance of response. It may also spare patients with a low chance of response the exposure to a therapeutic agent that they may not respond to and also spare them the side effects of such agent …”
Section: Discussionmentioning
confidence: 99%
“…It may also spare patients with a low chance of response the exposure to a therapeutic agent that they may not respond to and also spare them the side effects of such agent. (25,26) In this study, we identified several genetic variants associated with NASH resolution and fibrosis improvement in participants in the FLINT trial. To our knowledge, except for variants in MAPK10, which were previously reported to be associated with liver enzymes levels in another GWAS, (27) the other variants and nearby genes identified in this study had not been previously reported to be associated with NASH or with response of liver disease to therapeutic agents ( Supporting Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many challenges in the real world in achieving recommended weight loss of even 7%‐10% of baseline body weight. These barriers include but are not limited to lack of patient motivation, variation in patient response to weight loss interventions, and physician time constraints in their busy respective practices . Some of the strategies to implement lifestyle modification are referral to trained lifestyle modification counsellors such as dietitians, physical activity supervisors and psychologists .…”
Section: Discussionmentioning
confidence: 99%
“…These barriers include but are not limited to lack of patient motivation, variation in patient response to weight loss interventions, and physician time constraints in their busy respective practices. 21,22 Some of the strategies to implement lifestyle modification are referral to trained lifestyle modification counsellors such as dietitians, physical activity supervisors and psychologists. 23,24 However, given the huge disease burden, these resources are not often available to many patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, blocking cholesterol synthesis at the lanosterol 14α-demethylase (CYP51) step leads to the prepubertal onset of liver injury with ductular reaction and fibrosis and a pronounced male prevalent liver dysfunction before puberty [10]. In young adults, the liver damage was more prominent among female mice due to diminished cholesterol esters and elevated sterol substrates [11].…”
Section: Introductionmentioning
confidence: 99%